The adventures of Little Archie - Bolling, Bob 1928- (Archie Comic Publication, 2008)
Follows the adventures of Little Archie who deals with Martian invaders, secret spies, pirates, and gorillas on the loose
Keywords: Andrews, Archie (Fictitious character) / Comic books, strips, etc; Graphic novels; Comic books, strips, etc; Comic